The Marshall Lerner Condition and Money Demand: A Note - SACCAL, Alessandro (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022, 2022)
What are the respective effects of a unit increase in money demand on the real exchange rate and on the current account, all else equal? The real exchange rate is known to appreciate, but the current account need not deteriorate, as the canonical Marshall Lerner condition instead seems to suggest. As this work presents, the current account deteriorates by virtue of a real exchange appreciation due to a fall in the real money supply, all else equal, and vice versa; it further specifies that the current account improves by virtue of a real exchange rate appreciation due to a rise in money demand, all else equal, and vice versa.